2009
DOI: 10.1080/15377900802484141
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Relationship Among Different Dimensions of Trait Anxiety, Demographic Variables, and Self-Reported School Adjustment in Elementary and Secondary School Students

Abstract: The purpose of this exploratory study was to examine the relationship among different dimensions of trait anxiety (social concerns, physiological anxiety, and worry/oversensitivity), demographic variables (age and gender), and school adjustment (attitude to school and attitude to teachers) in children and adolescents. The study participants, consisting of 206 children and adolescents (100 males and 106 females), ages 9 to 19, in grades 4 through 12, completed several self-report measures of anxiety and school … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
1
8
0
1
Order By: Relevance
“…Similar to Witteborg et al (2009) findings with a sample of students without SLD, the present study's findings indicate that the RCMAS-2 Physiological Anxiety and Social Anxiety scores were significant predictors of the BASC-2-SRP Attitude to School scores, such that those Unstandardized regression coefficients (b), standardized (b) beta weights, and the standard error of the unstandardized beta weights (SE b) are displayed for each variable. DR 2 represents the amount of the variance accounted for by the variables within that step of the analysis * p \ .05; ** p \ .01 Unstandardized regression coefficients (b), standardized (b) beta weights, and the standard error of the unstandardized beta weights (SE b) are displayed for each variable.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Similar to Witteborg et al (2009) findings with a sample of students without SLD, the present study's findings indicate that the RCMAS-2 Physiological Anxiety and Social Anxiety scores were significant predictors of the BASC-2-SRP Attitude to School scores, such that those Unstandardized regression coefficients (b), standardized (b) beta weights, and the standard error of the unstandardized beta weights (SE b) are displayed for each variable. DR 2 represents the amount of the variance accounted for by the variables within that step of the analysis * p \ .05; ** p \ .01 Unstandardized regression coefficients (b), standardized (b) beta weights, and the standard error of the unstandardized beta weights (SE b) are displayed for each variable.…”
Section: Discussionsupporting
confidence: 81%
“…Kirkpatrick-Johnson et al (2006) suggested that older students have poorer school adjustment than younger ones, which could be due to junior high and high school students having more compartmentalized classes or spending less time connecting with a single teacher or peer group. However, Witteborg et al (2009) found that younger students and those with more social anxiety tended to have poorer attitudes toward their teachers. Despite the fact that students with SLD tend to have lower school adjustment (Tur-Kaspa and Bryan 1995) and higher levels of self-reported anxiety (Greenham 1999;Margalit and Raviv 1984;Nelson and Harwood 2011;Wilson et al 2009) than peers without SLD, to date, no study has examined school adjustment and dimensions of anxiety within the SLD population.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…La présence d'anxiété peut avoir de nombreuses conséquences chez les jeunes en milieu scolaire : conflits avec les pairs, problèmes de concentration, ainsi qu'un taux d'absentéisme plus élevé, ce qui peut mener à des difficultés d'apprentissage et à un risque de décrochage scolaire (Essau, Conradt et Petermann, 2000 ;Kim-Cohen et al, 2003 ;Witteborg, Lowe, Lee et Steven, 2009). Une étude de la National Comorbidity Survey (Merikangas et al, 2010) évalue la présence d'anxiété globale à 31,4 % chez les 13-14 ans.…”
Section: L'anxiétéunclassified